VERBAL EXPRESSION OF EMOTIONS IN PHRASEOLOGY - K. Y. Shcherbakov (Вестник Кемеровского государственного университета, 2013)
The article deals with emotive lexis of modern English, which discloses universal features of human verbal abilities, culturally determined differences in its organization and functioning, linguistic reflection of correlation of emotions and psycho-physiological condition of human body.